50 Years of the Journal of the Brazilian College of Surgeons: History, Evolution and Future Prospects - GERSON ALVES PEREIRA JUNIOR; ANDREIA CRISTINA FEITOSA DO CARMO; JULIA CASTRO NEVES; RAMIRO COLLEONI NETO (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT This article celebrates the 50th anniversary of the continuous publication of the Journal of the Brazilian College of Surgeons (RCBC), revisiting its trajectory from the beginning to the present day. RCBC has evolved from a nationally relevant publication to a journal with international impact, constantly adapting to changes in editorial and scientific practices. This article presents an analysis of the major milestones, editorial changes, and innovations that have cemented RCBC as a prominent scientific vehicle. In addition, it discusses future strategies to maintain editorial quality and increase the visibility of the journal in the global scientific scenario.